Feasibility of arm‐draining lymph node‐sparing radiotherapy of breast cancer: A pilot planning study. Issue 7 (24th August 2021) - Waldstein, Cora; Moodie, Trevor; Ashworth, Simon; Ahern, Verity; Stuart, Kirsty; Wang, Wei
Abstract: Introduction: Lymphoedema following axillary radiotherapy for breast cancer causes significant morbidity. Our goal was to evaluate the feasibility of sparing the lymph node that drains the arm's lymphatics (ARM node) while achieving standard dose constraints for whole breast and comprehensive lymph node irradiation. Methods: Six patients underwent lymphoscintigraphy and SPECT CT to identify the breast sentinel node (SN) and ARM node. The ARM node was contoured on the SPECT CT and deformably registered to the radiotherapy treatment planning CT. Radiotherapy plans (50 Gy in 25 fractions) with VMAT technique were generated, with the aim to spare the ARM node (Mean dose <25 Gy) and achieve adequate coverage to the remaining axilla. The plan required the breast SN site (clip + 10 mm surrounding the clip) to achieve D98% > 47.5 Gy, and axillary nodal CTV excluding ARM node to achieve D90% > 45 Gy. Results: In one patient, the ARM node was within the volume of breast SN site and sparing was not possible. For the remaining 5 patients, an ARM node‐sparing plan could be successfully generated; the mean dose to the ARM node ranged from 11.2 to 23.1 Gy (median 13.8 Gy). In these 5 subjects, D90% > 45 Gy of axillary nodal CTV (range, 44.9–48.5 Gy, median 46.2 Gy) and D98% > 47.5 Gy of breast SN site were achieved. Conclusion: In this planning study, ARM node‐sparing VMAT of the breast and lymph nodes was feasible, while maintaining adequate dosimetric coverage. However, in some individuals, localization of the ARM node in close proximity to breast SN site precluded the generation of an ARM node‐sparing treatment plan.